Market trends and analysis of blockchain technology in supply chain - Thakur, Anusha (Frontiers in Blockchain, 2023)
Technology poses to be an important tool in the armory of state-of-the-art innovations, in terms of both digital expansions, and disruptions. With blockchain technology gaining momentum, different industries emphasize on experimenting with the technology. Organizations nowadays are emphasizing towards agile and leaner supply chains with end-to-end prominence via the incorporation of this latest technology, thereby boosting the services across the world. The revolutionary features of blockchain technology are paving way for larger opportunities for supply chain businesses. The technology owes the ability to become the supply chain data utility and repository offering benefits to all the users, such as unique market information which was otherwise unavailable from any other source. This paper contemplates the need for blockchain technology in the supply chain and its contribution to enhancing businesses' overall efficiency and demand planning processes. It discusses the latest market trends and factors driving the need for the incorporation of blockchain in the supply chain sector and the future scenario for the same. Different use cases of the technology, market challenges in the implementation of the technology, and the solutions offered by different companies to cater to such problems have also been discussed.